2012
DOI: 10.1016/j.cub.2012.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Growth in width and FtsZ ring longitudinal positioning in a gammaproteobacterial symbiont

Abstract: Rod-shaped bacteria usually grow in length and place their FtsZ ring and division site at midcell, perpendicular to their long axis [1,2]. Here, we provide morphometric and immunocytochemical evidence that a nematode-associated gammaproteobacterium [3,4] grows in width, sets a constricting FtsZ ring parallel to its long axis, and divides longitudinally by default. Remarkably, the newly described FtsZ ring appears to be not only 90° shifted with respect to model rods, but also elliptical and discontinuous. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 10 publications
1
68
0
1
Order By: Relevance
“…We showed that the Z-ring is not a smooth structure but instead comprises clusters of FtsZ protofilaments that loosely associate into a 3D bundle (19,48). This heterogeneous morphology has also been observed with several different fluorescent protein tags (19), in different bacterial species (51)(52)(53)(54), by immuno-superresolution imaging targeting native FtsZ (19,54), by superresolution imaging of FtsZ-binding proteins (19,54), and in an early electron cryotomography (ECT) study (37). Here, we further demonstrate that an FtsZ-GFP fusion colocalizes with native FtsZ in midcell clusters in two-color superresolution imaging using antibodies against native FtsZ and GFP (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We showed that the Z-ring is not a smooth structure but instead comprises clusters of FtsZ protofilaments that loosely associate into a 3D bundle (19,48). This heterogeneous morphology has also been observed with several different fluorescent protein tags (19), in different bacterial species (51)(52)(53)(54), by immuno-superresolution imaging targeting native FtsZ (19,54), by superresolution imaging of FtsZ-binding proteins (19,54), and in an early electron cryotomography (ECT) study (37). Here, we further demonstrate that an FtsZ-GFP fusion colocalizes with native FtsZ in midcell clusters in two-color superresolution imaging using antibodies against native FtsZ and GFP (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 77%
“…These studies support a smooth, continuous Z-ring organization. However, Z-ring discontinuity has been observed in many bacterial species (19,37,48,(51)(52)(53)(54), and incomplete Z-rings have been shown to lead to cell wall indentation (110), suggesting that ring completion is not required for Z-ring function. We suggest that the continuous and discontinuous organizations reflect different dynamic states of the Z-ring modulated by FtsZ's GTPase activity, which is known to promote the fracture of long FtsZ polymers (111) and to modulate FtsZ turnover dynamics (82).…”
Section: Discussionmentioning
confidence: 99%
“…After the self-assembly the Z-ring starts to constrict, thereby directing the division of the cell, which results in two equal daughter cells. Given that FtsZ mediates binary fission in all known Gammaproteobacteria , including the longitudinally dividing MONTS associated with Laxus oneistus 31, and it is part of the genetic repertoire of three additional MONTS (genome drafts available upon request at http://rast.nmpdr.org/rast.cgi), we hypothesized that Efs and Eds also express the fts Z gene. By using degenerate PCR primers on gDNA extracted from single symbiotic nematodes, we homology cloned Efs and Eds ftsZ -gene fragments.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers also found that the Min oscillations scaled according to cell size across a wide range of sizes, thereby enabling robust division-site placement as cells grow. Furthermore, in some rectangular geometries, the Min system oscillated over the shortest lateral distance, a striking observation given the recent report of a rodshaped bacterial symbiont that divides along its long axis 8 .…”
Section: News and Viewsmentioning
confidence: 93%